Assessment of videos related to lung nodules in China - Han, Jiajun; Shi, Yifan; Ma, Haitao (Frontiers in Surgery, 2022)
Background: With the popularization of mobile phones and the development of the Internet, many patients use social media platforms to seek health information. Currently, TikTok, iQiyi, Bilibili, and Weibo are the most popular video platforms in China. Therefore, based on the above facts, this study estimated the quality of lung nodule videos taken in China using these platforms. Methods: The term “lung nodule” was searched on these platforms. Then, the first 30 videos were selected. Subsequently, some videos were excluded after they had been reviewed and analyzed, after which information on the features and sources of these videos was finally assessed using DISCERN, the Journal of the American Medical Association (JAMA) Benchmark Criteria, and the Hexagonal Radar Schema. Analysis was performed according to different groups. Results: 101 videos were included in this study. According to the different sources, although most videos were from physicians (71.3%), comprising those with shorter durations; faster updates; and more likes, comments, and shares; no significant difference in the scores were obtained. Moreover, regarding the different platforms, while Weibo had the highest update, TikTok had more likes, comments, and shares. Investigations also revealed that while score differences were recorded, most videos were rated “very poor” and “poor.” Besides, hexagonal radar charts showed a severe deficiency of video information. Conclusions: Although the quality of most videos on the understudied social media platforms was poor, these platforms have huge potential. Therefore, caution should be exercised when using the platforms as information sources about lung nodules, and a better review and push system is needed.